2015
DOI: 10.2174/1874210601509010154
|View full text |Cite
|
Sign up to set email alerts
|

Squamous Odontogenic Tumor: Literature Review Focusing on the Radiographic Features and Differential Diagnosis

Abstract: Since its first publication in 1975, the squamous odontogenic tumor remains the rarest odontogenic lesion, with around 50 cases in the English-language literature in which the microscopic characteristics are frequently very well demonstrated. However, articles which discuss the radiographic aspects are scarce, especially with emphasis on the differential diagnosis. The present treatise proposes an assessment of jaw lesions with the same radiographic characteristics of the squamous odontogenic tumor to clarify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…The lucent area has a wide base between the diverging apices of the affected tooth roots. 31 The tumor in the present case closely resembled SOT of humans in clinical presentation and behavior and exhibited typical histopathological and radiological features. The dog in the present case presented for routine dental care without evidence of an oral tumor and without apparent pain or discomfort.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The lucent area has a wide base between the diverging apices of the affected tooth roots. 31 The tumor in the present case closely resembled SOT of humans in clinical presentation and behavior and exhibited typical histopathological and radiological features. The dog in the present case presented for routine dental care without evidence of an oral tumor and without apparent pain or discomfort.…”
Section: Discussionsupporting
confidence: 69%
“…Although SOT is locally invasive, local recurrence is rare and distant metastasis has not been reported. [15][16][17][18]20,31,30 This case illustrates the importance of computed tomography (CT) for tumor excision surgical planning. 24,25,33 In this case, CBCT was utilized.…”
Section: Discussionmentioning
confidence: 99%
“…Squamous odontogenic tumor is a rare odontogenic tumor, since until today no more than 110 cases have been described and confirmed [5,6,8,9,12,13,14]. There is no sex or age predilection, but it seems that the Caucasian race is more frequently involved [12].…”
Section: Discussionmentioning
confidence: 99%
“…The differential diagnosis based on the clinical and radio-graphic appearance of the tumor includes dentigerous cyst, odontogenic keratocyst, periodontal cyst, radicular cyst, adenomatoid odontogenic tumor, central odontogenic fibroma, hematological disorders, ameloblastoma and more rare other odontogenic tumors or metastasis [2,3,5,9,11,15,16]. It has been found that SOTs located in the maxilla behave more aggressively than in the mandible, due to the anatomy of the area and the porous, medullary nature of the bone.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, SOTs present as a slow growing lesion leading to gradual increase in the volume of the maxilla or mandible, tooth mobility and displacement, sometimes ulceration. Radiologically, a broad list of possible diagnoses include developmental or noninflammatory odontogenic cysts, inflammatory odontogenic cysts, odontogenic tumors, hematological disorders, such as Langerhan's cell histiocytosis and multiple myeloma and bone pathology, such as central giant cell lesion and metastasis [7] . The classical radiological finding shows a unilocular and triangular shaped radiolucency of the alveolar bone, with wide base: the radiolucency localized between the diverging apices of the adjacent roots [8] .Grossly the tumor size varies and depends on the duration of the tumor.…”
Section: Discussionmentioning
confidence: 99%